SOFIA/HAWC+ observations of the Crab Nebula: dust properties from polarized emission. Issue 3 (26th August 2022) - Chastenet, Jérémy; De Looze, Ilse; Hensley, Brandon S; Vandenbroucke, Bert; Barlow, Mike J; Rho, Jeonghee; Ravi, Aravind P; Gomez, Haley L; Kirchschlager, Florian; Macías-Pérez, Juan; Matsuura, Mikako; Pattle, Kate; et al.
ABSTRACT: Supernova remnants (SNRs) are well-recognized dust producers, but their net dust production rate remains elusive due to uncertainties in grain properties that propagate into observed dust mass uncertainties, and determine how efficiently these grains are processed by reverse shocks. In this paper, we present a detection of polarized dust emission in the Crab pulsar wind nebula, the second SNR with confirmed polarized dust emission after Cassiopeia A. We constrain the bulk composition of the dust with new SOFIA/HAWC+ polarimetric data in band C 89 μm and band D 154 μm. After correcting for synchrotron polarization, we report dust polarization fractions ranging between 3.7–9.6 per cent and 2.7–7.6 per cent in three individual dusty filaments at 89 and 154 μm, respectively. The detected polarized signal suggests the presence of large (≳0.05–0.1 μm) grains in the Crab Nebula. With the observed polarization, and polarized and total fluxes, we constrain the temperatures and masses of carbonaceous and silicate grains. We find that the carbon-rich grain mass fraction varies between 12 and 70 per cent, demonstrating that carbonaceous and silicate grains co-exist in this SNR. Temperatures range from ∼40 to ∼70 K and from ∼30 to ∼50 K for carbonaceous and silicate grains, respectively. Dust masses range from ∼10 −4 to ∼10 −2  M⊙ for carbonaceous grains and to ∼10 −1  M⊙ for silicate grains, in three individual regions.